Pengaruh Pengembangan Karir Dan Pemeliharaan Sumber Daya Manusia (SDM) Terhadap Produktivitas Kerja Karyawan (Studi Pada Perusahaan Manufaktur di Pasuruan) - Rachmita Dwi Novianti; Abdul Kodir Djaelani; Ratna Tri Hardaningtyas (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to determine the effect of career development and maintenance of human resources (HR) on employee productivity. This research uses quantitative methods. The data collection method in this study used a questionnaire with a total sample of 129 employees. The data analysis method used in this study is multiple linear regression analysis with hypothesis testing using the F test and t test. Based on the results of the analysis and discussion, the conclusions that can be drawn are as follows. (1) Based on the results of the F test, it is concluded that Career Development and Maintenance of Human Resources (HR) have a simultaneous influence on Employee Work Productivity, (2) The results obtained in this study can be concluded that partially Career Development has a significant positive effect on Work Productivity Employees, (3) The results obtained in this study can be concluded that partially Maintenance of Human Resources (HR) has a significant positive effect on Employee Work Productivity. Keywords: Career Development, Maintenance of Human Resources (HR), Employee Productivity